Food for all global agriculture and the developing world - Sanchez Gallo, Jorge; Rodriguez, Chema; Films For The Humanities & Sciences (Firm). (Hamilton, NJ : Films for the Humanities & Sciences, 2008)
Satisfying one's hunger is a primal act which most Westerners never connect to global issues. But the diets and farming systems of wealthy countries can be directly linked to starvation in the underdeveloped world. This program sheds light on the international tragedy of hunger and malnutrition, emphasizing that the problem is one of distribution, not production.
[j.1]. Global dump: toxic waste and the planetary ecosystem -- [j.2]. A world apart: global inequality and its consequences -- [j.3]. Food for all: global agriculture and the developing world -- [j.4]. Who's destroying the forest? A global analysis -- [j.5]. Over-exploiting the oceans: the dangers of over-fishing.
Volume numbers assigned by cataloger in the order of the publisher's item numbers.
DVD format.
Keywords: Food supply; Food supply -- Developing countries; Agriculture; Obesity -- United States; Hunger -- Developing countries; Malnutrition -- Developing countries; Green Revolution; Food supply